1998
DOI: 10.1111/j.1469-7793.1998.883bd.x
|View full text |Cite
|
Sign up to set email alerts
|

Efferent projection from the preoptic area for the control of non‐shivering thermogenesis in rats

Abstract: To investigate the characteristics of efferent projections from the preoptic area for the control of non‐shivering thermogenesis, we tested the effects of thermal or chemical stimulation, and transections of the preoptic area on the activity of interscapular brown adipose tissue in cold‐acclimated and non‐acclimated anaesthetized rats. Electrical stimulation of the ventromedial hypothalamic nucleus (VMH) elicited non‐shivering thermogenesis in the brown adipose tissue (BAT); warming the preoptic area to 41.5 °… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(101 citation statements)
references
References 29 publications
(33 reference statements)
7
94
0
Order By: Relevance
“…In addition, another pathway through the dorsomedial hypothalamic nucleus was also proposed to transmit POA-derived pyrogenic PGE 2 signals . Other reports showed that warming of the POA abolished BAT thermogenesis evoked by stimulation of a hypothalamic region (Chen et al, 1998) and that this inhibitory effect by POA warming was antagonized by bicuculline injection into the raphe pallidus nucleus (Taniguchi et al, 2003). These findings suggest that the pyrogenic and heat-gain signals from the POA are conveyed to rostral medullary raphe regions and activate VGLUT3-expressing neurons therein.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In addition, another pathway through the dorsomedial hypothalamic nucleus was also proposed to transmit POA-derived pyrogenic PGE 2 signals . Other reports showed that warming of the POA abolished BAT thermogenesis evoked by stimulation of a hypothalamic region (Chen et al, 1998) and that this inhibitory effect by POA warming was antagonized by bicuculline injection into the raphe pallidus nucleus (Taniguchi et al, 2003). These findings suggest that the pyrogenic and heat-gain signals from the POA are conveyed to rostral medullary raphe regions and activate VGLUT3-expressing neurons therein.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, PGE 2 is considered to act on the EP3 receptor of POA neurons and trigger fever. The POA is also known as one of the major central thermosensitive sites to monitor deep body temperature: cooling of this region causes nonshivering thermogenesis (Banet et al, 1978;Imai-Matsumura et al, 1984), possibly as a result of suppression of warmsensitive neurons (Chen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The currently accepted model of thermoregulation is that both heat production and heat loss are under tonic inhibitory control by warm-sensitive preoptic neurons (Zhang et al, 1995;Chen et al, 1998;Nagashima et al, 2000;Osaka, 2004;Rathner et al, 2008;Tanaka et al, 2009), with those regulating heat production projecting to the DMH and those regulating heat dissipation projecting directly to the medullary raphé (Nakamura and Morrison, 2007;Morrison et al, 2008;Rathner et al, 2008). No significant output from the preoptic region has been attributed to coldsensitive cells.…”
Section: Tail Sympathetic Nerve Fiber Recordingmentioning
confidence: 99%
“…Cooling of this area activates BAT ( 62,63 ), whereas warming suppresses its activity ( 64 ). The signal is mediated through the VMH and medulla oblongata and then passes through the spinal cord until it reaches the relevant IML neurons ( 65 ).…”
Section: Sympathetic Innervation Of Batmentioning
confidence: 99%